A companion to diaspora and transnationalism - Quayson, Ato. (Hoboken, NJ : Wiley-Blackwell, 2013)
'A Companion to Diaspora and Transnationalism offers a ground-breaking combined discussion of the concepts of diaspora and transnationalism. Newly commissioned essays by leading scholars provide interdisciplinary perspectives that link together the concepts in new and important ways. A wide-ranging collection which reviews the most significant developments and provides valuable insights into current key debates in transnational and diaspora studies Contains newly commissioned essays by leading scholars, which will both influence the field, and stimulate further insight and discussion in the future Provides interdisciplinary perspectives on diaspora and transnationalism which link the two concepts in new and important ways Combines theoretical discussion with specific examples and case studies'--
Includes bibliographical references and index.
Keywords: Human beings -- Migrations; Human geography; Transnationalism; Emigration and immigration